A Community based Study of Anaemia Burden using Hemocue 201 in Eastern India - Bhatia, Vikas; Parida, Swayam Pragyan; Mahajan, Preetam B; Sahoo, Durgesh Prasad; Bhattacharjee, Sourav (Indian Journal of Community Health, 2020)
Background: India is facing a serious burden of anemia where majority of the women (51%) of reproductive age suffer from anemia. Though there are many programs being run for decades to fight anaemia, it still persist to be a major health challenge in Odisha where around half of the women and children are anemic (children age 6-59 months; 44.6%, pregnant women of age 15-49; 47.6%, all women of age 15-49 years; 51.0%). Objectives: AIIMS Bhubaneswar, in partnership with Govt. of Odisha and UNICEF aimed to assess the burden of anaemia in the state. Methods: This cross-sectional study was conducted amongst 3974 beneficiaries between March to July 2016. Hemoglobin estimation was done using Hemocue 201. Results: Prevalence of mild, moderate and severe anemia was observed to be 39-58%, 7-20% and 1-3%, respectively in 4 districts. Coverage of iron folic acid tablets amongst adolescent girls, adolescent boys, pregnant women, lactating mothers, and women of reproductive age groups were 38%, 16%, 73%, 46%, 11% respectively. Conclusion: The study has shown that prevalence of severe and moderate anaemia has decreased to a greater extent, however the prevalence of mild anaemia is still very high.